Rethinking Conscientious Objection to Mandatory Vaccination - Tucak, Ivana; Berdica, Josip (Review of European and Comparative Law, 2024)
Among the member states of the Council of Europe, there is a consensus on the importance of vaccination as a successful and effective preventive health intervention. Every state aims to achieve herd immunity, i.e., a high vaccination rate of the population that will prevent the circulation of contagious diseases in the population and thus protect those who cannot be vaccinated due to age or poor health. However, despite the general recognition of the importance of vaccination, there is no consensus on a “single model” of how best to achieve the goals of mass immunization. Countries have different public health policies, so while the vaccination policy of some members of the Council of Europe is limited to a recommendation, others have made vaccination compulsory. Today, there are many opponents of vaccination and those who are hesitant. This paper will focus on those who refuse to be vaccinated based on a moral understanding of how to act in certain circumstances. The paper will explore whether countries imposing mandatory vaccination, with financial or other sanctions imposed in the case of non-compliance, should recognize the right to conscientious objection. This includes the right of adults to refuse vaccination, and respecting the religious and philosophical beliefs of parents who refuse to vaccinate their children. The article consists of two main parts. The first part will explore the legal-theoretical and legal-philosophical dimensions of the relationship between justice and conscience, with special emphasis on the interpretation of this relationship provided by the American political philosopher John Rawls. The second part of the paper will examine the issue of compulsory vaccination and conscientious objection through the prism of the rights provided for in the Convention for the Protection of Human Rights and Fundamental Freedoms.